Economic Value of Forest Hydrological Benefit of Musi Watershed: Case of Perapau Sub Watershed - Nur Arifatul Ulya (Indonesian Journal of Geography, 2019)
Forest area in upper Perapau sub watershed that provide a hydrological benefit for community living surrounding are now partially converted to plantations, dry land farms and paddy fields, whereas the forests are part of protected forest and wildlife reserve. The land cover change occurs due to lack of understanding about economic value of hydrological benefits of forests in the Perapau sub watershed. This study aims to determine the economic value of hydrological benefits of forests in Perapau sub watershed. Procurement cost method used to estimate the economic value of the hydrological benefits of the Perapau sub watershed.  The economic value of hydrological benefits for household and agricultural purposes is 1.712 trillion rupiah and 11.056 billion rupiah. Based on the economic value of hydrological benefit, sustainability of forest in the upstream of Perapau sub watershed must be supported for sustainability of hydrological services of watershed.